Certified reference materials for effective automotive diesel fuel testing. (15th February 2021) - Ulberth-Buchgraber, Manuela; Charoud-Got, Jean; Held, Andrea
Highlights: Two new certified reference materials (CRMs) for diesel testing. Use of standard methods for diesel monitoring (EN 590) do not per se guarantee reliable measurement results. CRMs allow to check the correct implementation of standard methods. Usage of CRMs together with available standard methods assure quality of measurement results. Abstract: In recent years, quality requirements of automotive diesel fuel have become considerably important. In the European Union fuels may only be placed on the market if they comply with the specifications set out in the fuel quality directive. Member States have to monitor compliance with the requirements using analytical methods, which are laid down in the European standard EN 590. The availability and use of these standard methods do not per se guarantee reliable measurement results. It is widely accepted that laboratories need to demonstrate their proficiency in the application of standard methods. Certified reference materials are the preferred tool to give laboratories the possibility to demonstrate their proficiency in applying the standard and proper working of their instruments. To meet this need, the Joint Research Centre of the European Commission has released two new certified reference materials (ERM®-EF003 and ERM®-EF004) for automotive diesel fuel containing 7% biodiesel, which will support fuel producers and fuel testing laboratories in assuring the quality of their measurements. Without underestimating the role and importance of other quality control tools, the current paper provides information (i) on steps taken to produce these certified reference materials and (ii) on their proper usage.